1979
DOI: 10.1111/j.1365-2133.1979.tb15285.x
|View full text |Cite
|
Sign up to set email alerts
|

PUVA-induced repigmentation of vitiligo: a histochemical (split-DOPA) and ultrastructural study

Abstract: Repigmentation induced by oral photochemotherapy (8-MOP + UV-A) in four patients with vitiligo has been studied by histochemical and ultrastructural techniques. Hypertrophic melanocytes were demonstrated both in the middle and deep portions of the hair follicles in the centre of islands of repigmentation and also in the epidermis of the expanding repigmenting border. Mitosis of melanocytes was absent in these areas. Ultrastructural study showed that the melanocytes of repigmented areas were hyperactive. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 18 publications
3
62
0
Order By: Relevance
“…The main reservoir of melanocytes is the hair follicle, in particular the external root sheath. 2,3 This is supported by the clinical observation that the face and neck have the maximum response rate to medical therapies, followed by proximal extremities and trunk. Acral parts of extremities and nonhairy areas such as the wrist, feet and male genitals respond poorly.…”
Section: What Does This Study Add?mentioning
confidence: 63%
“…The main reservoir of melanocytes is the hair follicle, in particular the external root sheath. 2,3 This is supported by the clinical observation that the face and neck have the maximum response rate to medical therapies, followed by proximal extremities and trunk. Acral parts of extremities and nonhairy areas such as the wrist, feet and male genitals respond poorly.…”
Section: What Does This Study Add?mentioning
confidence: 63%
“…Studies demonstrated that loss of McSCs leads to hair graying (42). Also, bulge McSCs are implicated in repopulating epidermal melanocytes during the recovery process of vitiligo, a disease characterized by skin depigmentation due to a loss of mature skin melanocytes (53). How McSC behavior is coordinately regulated with HFSCs throughout the hair cycle has recently been examined.…”
Section: Stem Cell Interactions Within the Niche -Another Playermentioning
confidence: 99%
“…usually after 1 week) phototherapy was used to induce proliferation and migration of melanocytes in the recipient sites. (29)(30)(31) The repigmentation rate in these studies according to the review by Njoo et al was 87%, whereas Ozdemi et al reported rates between 25% -65%. (29)(30)(31)(32)(33)(34)(35)(36) In the study by Maleki et al, ten patients with refractory vitiligo who were treated by suction blister graft and subsequent PUVA therapy reported over 90% repigmentation in seven patients.…”
Section: Discussionmentioning
confidence: 89%